Analysis of fine grained sand and shale sedimentary characteristics in estuary based on sediment dynamics - Zhang, Chaoqian; Hu, Yongle; Wu, Suwei; Tang, Mingming; Zhang, Kexin; Chen, Heping; Wan, Xuepeng; Huang, Wensong; Han, Di; Meng, Zheng (Frontiers in Earth Science, 2023)
Due to the dual effects of fluvial and tides, the tidal sand bars in estuaries have complex sedimentary characteristics and complex internal structures, making them difficult to predict and describe. In this paper, the sedimentary dynamics numerical simulation method is used to establish a tidal-controlled estuary model. The effects of tidal range and sediment grain size on tidal sand bars are simulated. The length, width, and thickness of tidal sand bars, as well as the length and thickness of the internal shale layer, are also analyzed. The results show that in the environment of a tide-controlled estuary, the tidal range has a more significant effect on tidal sand bars compared to the sediment grain size under the specific conditions used in this study. The main effect of tidal range on tidal sand bars is that the greater the tidal range, the greater the length-to-width ratio of the sandbank, and the higher the degree of sandbank development. In a tidal-controlled estuary environment, the formation and distribution of shale layer structures are also affected by tides: the length of the shale layer increases as the tidal energy increases, but the changes in the thickness are not obvious. Numerical simulations of the development and distribution of the tidal sand bars and shale layers in estuaries based on sedimentary dynamics will provide a basis for the sedimentary evolution of tide-controlled estuaries and will provide guidance for the exploration and development of tidal estuaries.